Enrichment of Apple Slices with Bioactive Compounds from Pomegranate Cryoconcentrated Juice as an Osmodehydration Agent - M. E. Guerra-Valle; J. Moreno; S. Lillo-Pérez; G. Petzold; R. Simpson; H. Nuñez (Journal of Food Quality)
Pomegranate juice is an important source of bioactive compounds, and cryoconcentrated juice is an interesting osmodehydration agent to enrich a vegetal matrix. This investigation aimed to incorporate bioactive compounds from pomegranate cryoconcentrated juice into apple slices using osmodehydration (OD) assisted by pulse vacuum (PV) and ohmic heating (OH). The apple slices (3 × 4 × 0.5 cm) were osmodehydrated using a 47 °Brix pomegranate cryoconcentrated juice at 30, 40, or 50°C for 180 min with an electric field of 6.66 V/cm (50 V) and a 5 min pulsed vacuum. Over the time, all of the treatments applied to the apple slices increased the soluble solids and bioactive compounds compared with the fresh sample. PVOD/OH at 50°C had the highest content of total anthocyanin during processing, and the best results for the total flavonoids were obtained with OD/OH at 50°C and 40°C. The osmodehydration assisted by pulse vacuum and ohmic heating using a cryoconcentrated juice is a useful combined technique to acquire enriched vegetal samples with bioactive compounds.